GAMBARAN PERILAKU GIZI PRIMIGRAVIDA MUDA DI WILAYAH KERJA PUSKESMAS TANAH TINGGI KECAMATAN BINJAI TIMUR KOTA BINJAI TAHUN 2012 - Roseni Ginting; Ernawati Nasution; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Young primigravida means the first pregnancy in young age under 20 years old. The readiness of a woman to have pregnancy depends on physical, mental, emotion, psychological, social and economy preparation. A woman is called physically ready for pregnancy after completing its growth time with the age around 20 years old. The pregnancy in young age can be categorized as high risk because it is included in one of the frequent pregnants, close pregnancy, too old and too young for high morbidity leading into various complication in pregnancy and delivery. The objective of this research is to know nutrition behavior young primigravida in Health Centre of Tanah Tinggi Binjai City in 2012. This research was descriptive with cross sectional design. The population were all pregnant women for the first time under 20 years old for 36 persons in Health Centre of Tanah Tinggi Binjai City in 2012. The collected data was analyzed using computer program, presented in frequency distribution table and analyzed descriptively. The results of research showed that 55,6%  young primigravida had low knowledge, 44,4% had  low attitude. Energy consumption rate was 44,4% in medium category,  and 47,2% was  categorized low. Based on the results of research, it can be concluded that the behavior of young primigravida was categorized low. It is suggested for Health Department Binjai City to give counseling to add the knowledge of young primigravida regarding the socialization activity for nutrient and high risk of pregnancy in young age. Keywords : nutrition behavior, consumption pattern,  young  primigravida